The Importance of Continuous and Discrete Elements in Continuum Robots. (14th March 2013) - Cowan, Lara S.; Walker, Ian D.
In this paper, we examine key issues underlying the design and operation of robots featuring continuous body ("continuum") elements. We contrast continuum and continuum-like robots created to date with their counterparts in the natural world. It is observed that natural continuum locomotors or manipulators almost invariably rely on hard or discrete elements (in their structure or operation) in their interactions with their environment. We suggest innovations in continuum robot design and operation motivated by this observation, supported by experiments using the "Tendril" continuum robot. The results suggest new ways in which continuum robot operations could be significantly enhanced. In particular, the exploitation of "hard" and "discrete" environmental features can greatly enhance stability in continuum robot operations, compensating for inherent backbone compliance. Additionally, the incorporation of discrete behaviours (sweeping and striking with the backbone) can both compensate for imprecision in continuum robot control and enable new impulsive manipulation modes. We discuss the implications for the creation and potential application of novel hybrid continuum and discrete robots.